A textbook of economic theory - Stonier, Alfred W.; Hague, Douglas C. (London : Longmans, 1964)
This edition is aimed at providing a comprehensive discussion of the theory of economic growth. The book is designed for students with no previous knowledge of economic theory who wish to study the elements of the subject systematically. It is hoped that some parts of the book will also be useful to more advanced students.
Includes bibliographical references and index.
rpm 12/07/2017
Loans
Keywords: Economics